Arteriosclerotic Aneurysms of the Coronary Arteries: Surgical Treatment - Bricker, Donald L. (1987)
We infer from our experience in over 4,000 revascularization procedures that true arteriosclerotic aneurysms of the coronary arteries are even more rare than reported in the literature, that such aneurysms usually occur in association with severe occlusive disease of the coronary arteries, and that the best surgical approach is to excise or ligate the aneurysm rather than leave it in continuity with coronary arterial circulation and risk complications. We present both rationale and technique in support of this more radical therapeutic approach. (Texas Heart Institute Journal 1987; 14:23-30)